In-situ stress prediction in ultra-deep carbonate reservoirs of Fuman Oilfield, Tarim Basin of China - Yin, Guoqing; Wu, Kongyou; Ju, Wei; Qin, Yun; Qian, Ziwei; Xu, Ke; Lu, Zhongyuan; Wang, Peng; Liang, Xiaobai; Liang, Yan (Frontiers in Energy Research, 2023)
The Fuman Oilfield in Tarim Basin has great potential for ultra-deep carbonate oil and gas resources, and is an important area for future storage and production increase. The present-day in-situ stress field is critical during the exploration and development. However, no systemic investigations have been carried out in this oilfield. Therefore, in this study, the present-day in-situ stress field in the Ordovician carbonate reservoir is predicted and analyzed based on well log calculation and geomechanical numerical modeling. The results indicate that, 1) NE-SW-trending is the dominant horizontal maximum principal stress (SHmax) orientation. The vertical principal stress is the maximum principal stress, showing the Ordovician reservoir is under a normal faulting stress regime. 2) The distribution of in-situ stresses in the Ordovician carbonate reservoir is heterogeneous, which is mainly controlled burial depth and fault/fracture development. High stress magnitudes in the Yingshan Formation are mainly in the southeastern part of Fudong area, Fuman Oilfield. The present-day horizontal differential stress mainly ranges from 27 MPa to 30 MPa in the Yingshan carbonate reservoir. iii) Natural fractures are generally stale under the present-day in-situ stress state. Fractures that parallel to the SHmax orientation with high fracture dip angle are easier to be reactivated. The results are expected to provide geomechanical references for further oil and gas development in the Fuman Oilfield of Tarim Basin.